Peningkatan Kemampuan Literasi dan Numerasi di SDK Maubesi II Kabupaten Timor Tengah Utara - Botha, Hendrikus Hironimus; Fritantus, Yohanes; Naif, Yohanes Imanuel; Bria, Makarius Erwin (Jurnal PKM Manajemen Bisnis, 2024)
This community service activity aims to improve literacy and numeracy skills for students at Maubesi 2 Catholic Elementary School, Insana Fafinesu District, North Central Timor Regency. This community service is carried out in several stages, namely coordinating/communicating with the TTU Regency Education and Culture Office and the target school, conducting initial observations, designing a work program and discussing it with the school, implementing the work program and evaluating the implementation of the work program. The community service methods used are communication, observation and implementation of work programs and evaluation. Based on the results of the community service carried out, it was found that there was an increase in literacy and numeracy skills as demonstrated by the increase in reading, writing and arithmetic skills of students at Maubesi 2 Catholic Elementary School. This was realized through the availability of learning media that was able to arouse students' interest in learning, mentoring. and structuring the classroom and library environment so that it influences enthusiasm for learning and participating in learning.